EVALUATION OF ANTIMICROBIAL POTENTIAL OF DIFFERENT SOLVENT EXTRACTS OF SOME MEDICINAL PLANTS OF SEMI-ARID REGION - Padalia, Hemali; Rathod, Tejas; Chanda, Sumitra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Infections caused by microorganisms that have become resistant to commonly used antibiotics have become a major nuisance globally. The problem of microbial resistance is increasing rapidly, and therefore there is an urgent need to develop novel antimicrobial agents from a natural source. The aim of the present study was to evaluate the antimicrobial activity of different solvent extracts of aerial part of Alysicarpus procumbens, Fimbristylis dichotoma, Saccharum spontaneum, Suaeda nigra, and Typha angustifolia against pathogenic microorganisms. Methods: The extraction was done by individual cold percolation method using five solvents of different polarity, viz., petroleum ether, ethyl acetate, acetone, methanol, and water (aqueous). The antimicrobial activity was done by agar well diffusion method against Gram-positive and Gram-negative bacteria and fungi. Results: All the plant solvent extracts showed varied level of antimicrobial activity against different microorganisms. All extracts of five plants showed better antibacterial activity than antifungal activity; Gram-positive bacteria were more susceptible than Gram-negative bacteria. Conclusion: The polarity of solvent greatly influences extractive yield and antimicrobial activity of medicinal plants. The best activity was shown by solvent extracts of S. nigra. Hence, it can be considered as good source of antimicrobial agents.